A Coherent Tidal Datum for the Torres Strait - Metters, D. R.; Pedderson, R. I. (The International Hydrographic Review, 2011)
The Torres Strait is a complex waterway to the north of Australia linking the Arafura and Coral Seas. Sea level data from 13 islands were provided with the intention of validating the GPS extension of AUSGeoid98 to the Torres Strait. A comparison between the Australian Height Datum (AHD) determined from the AUSGeoid98 model and Mean Sea Level (MSL) identified differences of up to 1.57m. A coherent tidal datum was established with a seasonal adjustment to the long-term level from Thursday Island. The seasonally adjusted MSL from this study should be considered as an approximation of AHD in the Torres Strait.